Notice of Remains found under a Cairn, surrounded by upright stones, on the Farm of Burreldales, parish of Auchterless, Aberdeenshire, in a Letter to the Secretary (Proceedings of the Society of Antiquaries of Scotland, 1863)
The author reports on a cairn that he excavated in 1860, where the farmer recently removed the rest of the earth from over the site. He describes his original findings and then goes on to discuss the contents of the cist that the farmer found when he removed the cairn. He believes that several aspects of this site may be unique, although other members of the Society disagree. It is noted that some of the remains from this site probably belonged to a human skeleton.